Cellular Imaging Electron Tomography and Related Techniques (Biological and Medical Physics, Biomedical Engineering,, 2018)
This book highlights important techniques for cellular imaging and covers the basics and applications of electron tomography and related techniques. In addition, it considers practical aspects and broadens the technological focus by incorporating techniques that are only now becoming accessible (e.g. block face imaging). The first part of the book describes the electron microscopy 3D technique available to scientists around the world, allowing them to characterize organelles, cells and tissues. The major emphasis is on new technologies like scanning transmission electron microscopy (STEM) tomography, though the book also reviews some of the more proven technologies like electron tomography. In turn, the second part is dedicated to the reconstruction of data sets, signal improvement and interpretation.